Perancangan Sistem Informasi Penjualan Barang Pada UD. Milala Berbasis Web - Ginting Babo, Aris Franata; Lumbantoruan, Gortap; Perangin-angin, Resianta (Universitas Methodist Indonesia, 2024)
Design of a Goods Sales Information System at UD. Web-Based Milala is an effort to increase efficiency and accuracy in the process of selling goods in the company. This system is designed to make it easier to record, monitor and analyze sales in real-time via a web platform. By using web technology, this system provides better accessibility to users from various locations, enabling more effective management and fast decision making. Integration of sales features, stock items and analytical reports became the main focus in designing this system, so that UD. Milala can optimize operations and increase customer satisfaction.